Evaluation of the individual performance of the company's managerial personnel in modern conditions - Kovshik, V. I.; Cai, Yujin (Державний університет "Одеська політехніка", 2025)
The paper addresses the current challenges of managing managerial personnel performance in the context of globalization, digitalization, and an unstable business environment. It highlights the limitations of traditional performance evaluation methods, including subjectivity, bureaucracy, and declining trust from managers and employees. The study emphasizes the potential of artificial intelligence and automated analytical tools to enhance objectivity, reduce human bias, and improve decision-making quality in performance management. A comprehensive approach is proposed that combines traditional techniques with innovative technologies and differentiates performance assessment at various managerial levels. It is concluded that integrating modern technologies with new managerial practices can foster more effective and transparent performance management systems.

У роботі розглянуто сучасні проблеми управління результативністю управлінського персоналу в умовах глобалізації, цифровізації та нестабільного зовнішнього середовища. Визначено основні недоліки традиційних методів оцінки ефективності, зокрема їхню суб’єктивність, бюрократичність і низьку довіру з боку менеджерів та працівників. Показано можливості застосування штучного інтелекту та автоматизованих аналітичних інструментів для підвищення об’єктивності оцінки, зниження впливу людського фактора та покращення якості управлінських рішень. Запропоновано комплексний підхід до оцінювання результативності персоналу на різних рівнях управління із поєднанням традиційних та інноваційних методів. Зроблено висновок, що поєднання сучасних технологій і нових управлінських практик дозволить сформувати більш ефективні та прозорі системи управління результативністю.
Keywords: управління результативністю; оцінка результативності; менеджмент; управління персоналом; personnel performance; performance management; performance assessment; management